THE EFFECTIVENESS OF SKINCARE LAWS AND REGULATIONS CAN JEOPARDIZE THE CONDITION OF THE HUMAN BODY. - Jayady, Try (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2024)
Determining the law and liability of skincare manufacturers for skin health. Normative law is part of the research of the results of this regulatory system has a structure, structure, or basis, and parts that give shape and boundaries to the whole One type of deviant behavior, namely crime, still exists in society. The use of law as a way to solve this problem is expected to produce the right solution. The form and nature of a criminal offense or offense shows that it is fair, appropriate.